Method and Meaning in Holocaust-Knowledge Surveys - Bischoping, Katherine (Holocaust and genocide studies, 1998)
Holocaust-knowledge surveys attracted considerable public attention in 1993, when media reports stated that 22% of the American public appeared to deny the existence of the Holocaust. Once this disturbing result was explained by question-wording experiments (experiments that exposed difficulties with the wording of the questions), public-opinion researchers abandoned discussion of Holocaust-knowledge surveys. In retrospect, the discourse about these surveys appears to have been limited, overlooking critical assumptions about the methodologies and theoretical bases of Holocaust-knowledge surveys. In this paper, assumptions about the primacy of question-wording studies, the exclusion of emotions from definitions of knowledge, and the omission of critical-thinking skills from these definitions are identified with data from a multi-method study of Holocaust knowledge. The paper employs theoretical perspectives in Holocaust and genocide studies to search for alternative methods of conceptualizing and measuring knowledge, and to illustrate how methods and meaning could be better integrated.